The Influence of Promotional Product Quality and Design on the Decision to Purchase Aluminum Goods at the Amerta Aluminum Store: - Oktaviani, Kadek Clara; Rianita, Ni Made (ProBisnis : Jurnal Manajemen, 2024)
The purpose of this research is to determine the influence of product quality, promotion and design on purchasing decisions for aluminum products at the Amerta Aluminum store. The population of this research is all Amerta Aluminum shop consumers, both male and female. The sample used in this research was 55 customers. Data collection methods use questionnaire techniques and documentation techniques. The type of research used is quantitative research and the data analysis used is multiple linear regression analysis. The data analysis technique uses the IBM SPSS Statistics 25 application. The results of the study show that Product Quality has a positive and significant effect on Purchasing Decisions with t count > t table (2.392 > 1.675 with a mean significance level of 0.020 < 0.05. Promotion has a positive and statistically significant effect on Purchasing Decisions with a calculated t value > t table value (1.755 > 1.675) with a significance level of 0.036 < 0.05. And design does not have a positive influence on Purchasing Decisions but has a significant value on Purchasing Decisions for aluminum products at the Amerta Aluminum store significance for Purchasing Decisions with tcount < ttable (3,010 < 1.675) with a significance level of 0.004 < 0.05.